SERVANT LEADERSHIP PRINCIPLES IN COLLEGIAL LEVEL: EFL STUDENTS' REPORTED EXPERIENCES IN AFGHANISTAN - Jawad Golzar; Mir Abdullah Miri (Borys Grinchenko Kyiv Metropolitan University, 2020)
Servant leadership has been one of the most preferred styles of leadership in education due to its underlying principles. This exploratory study aimed to examine the university teachers' use of servant leadership principles by students' reported experiences. It utilized a mixed-method approach. A questionnaire was sent to 111 college students after conducting a pilot, passing the reliability test, and applying sample size formula. The semi-structured interviews were also taken from 11 participants who were sophomore and junior students in the English Department, Faculty of Letters and Humanities. The data was analyzed through color-coding, thematic and statistical analyses. This study narrowed its scope by only focusing on the principles of listening, persuasion, commitment to the growth of others, and community building. It tested the correlation between these principles and examined the relationships between the reported use, gender, and schooling years. The results revealed that the practiced servant leadership principles were pretty at a high level except for the commitment to others' growth principles (M= 3.6). It also found that gender was not a robust predisposing factor, whereas years of schooling influenced the students' reported experiences about their teachers' use of servant leadership in the classroom. The principles also proved to be correlated after conducting the Pearson correlation test. The study concluded with suggestions and further implications that could improve the quality of instruction in the classrooms and educational institutions. It is highly suggested to establish leadership centers in both public and private higher education institutions to provide various leadership trainings for students, teachers and staff to enhance the quality of education.